First-principles Study of Electronic and Magnetic Properties of Manganese Decorated Graphene (Journal of Nepal Physical Society, 2016)
The functionalization of graphene by the addition of Manganese (Mn) atom to its surface has been investigated computationally by using density-functional theory (DFT) based first-principles method within DFT-D2 level of approximations. The calculations have been computed employing the Quantum ESPRESSO codes. The stability, geometrical structures, electronic and magnetic properties of pure and Mn adatom graphene systems have been studied. From the information of adsorption energies of Mn atom on the different sites of graphene, the top site is found to be the most favorable one for its adsorption. Present study finds that the London dispersion interaction plays a major role in the weak binding of Mn on graphene. The study of electronic and magnetic properties of Mn decorated graphene shows that the conduction and valence band are overlapped with finite density of states (DOS) at Fermi level. The dissimilar DOS for up and down spin calculations quantify magnetic moment as 5.48 μB which is consistent with the previous studyJournal of Nepal Physical Society Vol.3(1) 2015: 24-34